Pola Rekrutmen Calon Anggota Legislatif Partai Golkar Pada Pemilu Legislatif Tahun 2019 di Provinsi Bali - Ni Luh Rosita Dewi Dewi; I Wayan Gede Suacana; Diah Rukmawati (Politicos: Jurnal Politik Dan Pemerintahan, 2023)
Political party is an institution or institution that functions as a pillar for the functioning of a representative democracy system. Political parties, through their recruitment function, play an important role in determining the people who will sit and carry out the functions of the country's political system through positions in existing government institutions. The purpose of this study is to describe the pattern of political recruitment carried out by the Golkar Party in the 2019 Legislative Elections. In the process of this research, the author adopted the recruitment theory put forward by Pippa Norris, using a descriptive qualitative analysis approach with the methods of observation, interviews, literature study, and documentation, which are then processed and written down as research data. In this research, the author focuses on the recruitment process carried out by the Golkar Party DPD Bali Province during the candidacy for members of the Provincial DPRD in the 2019 Legislative Election. At that time, the Golkar Party DPD Bali was also experiencing internal dynamics and was exposed to various issues. The results of this study indicate that carrying out the political recruitment agenda of the DPD Golkar Party itself is known as the assignment of functionaries, with three stages of recruitment, namely certification, nomination, and the election stage. Regarding formal legal certifications and requirements, the candidates have followed the good requirements mandated by law and the party. In the nomination stage, the Golkar Party tends to be exclusive only for cadres by applying certain criteria beyond the conditions set by the state. In terms of determining the final decision, even though the provincial DPD has determined 100% of prospective candidates, the final decision on determining the DPT is still determined by the central DPP.